How Intersectoral Health Promotion Changes Professional Practices: A Case Study From Denmark. Issue 5 (September 2018) - Christensen, Mads; Burau, Viola; Ledderer, Loni
Intersectoral health promotion (IHP) has pushed health professions to engage in new tasks and interprofessional ways of working. We studied how care assistants from a nursing home and school teachers implemented a cookery project targeted at children ("Cool Beans") as an example of an IHP project in Denmark. Our aim was to examine the impact of the IHP project on the practices of the professions involved. We used a qualitative case study to investigate joint care and teaching situations with the two professions and their users. Our data consisted of documents, participatory observations, and informal interviews (17 hours) as well as semistructured interviews with professionals (n = 4). We used a sociological institutional framework to analyze the professional practices emerging in joint care and teaching situations and identified three themes of new professional activities: (1) "interplay" related to making different generations collaborate on the tasks involved in the cookery session; (2) "care" concerned with caregiving activities; and (3) "learning" focused on schooling on healthy food and cooking. We conclude that changes in professional practices occurred informally and were induced by the concrete activities in the cookery project. The specific, practical tasks of the IHP project thus offered an important leverage for future interprofessional collaborations.